The Institutionalization of Political Humor as a Form of Reflection - S. S. Melnikov (Vestnik MGIMO-Universiteta)
The paper analyzes the genesis of modern political humor and determines its position in the system of spiritual relations in society. The formation of the need to comprehend social relations by means of humor during progressive transition from traditional to modern society is investigated. We note that humor is essentially a social phenomenon. A fundamental distinction between humor formed in the modern period and humor of previous times is the presence of reflexivity. New kind of humor has also dealt with political relations began to be interpreted by means of humor culture. In the course of research we found that comic interpretation of politics became feasible due to the legislative fixation of individual rights as a part of modern political culture. The emancipated personality demonstrates more complicated expectations to a political institute and experiences acute dissatisfaction as state authorities have often made decisions not appropriate to such expectations. For the individual as sovereign entity political humor became a sort of social and psychological compensation. An author pays attention to the fact that the social subject having shown such a reaction was formed during the second half of XIX and the beginning of XX centuries because of the dissemination of the print media and was named «the audience». The audience became a key agent of humorous reflection about the political institute. As a case that grounds the applicability of this theory to the practice the paper considers the example of inclusion of specific comic genre (political caricature) in the social discourse in the West and in Russia.